Assessing cell-nanoparticle interactions by high content imaging of biocompatible iron oxide nanoparticles as potential contrast agents for magnetic resonance imaging - Roxanne Hachani (Nature Portfolio, 2017)
Abstract Stem cell tracking in cellular therapy and regenerative medicine is an urgent need, superparamagnetic iron oxide nanoparticles (IONPs) could be used as contrast agents in magnetic resonance imaging (MRI) that allows visualization of the implanted cells ensuring they reach the desired sites in vivo. Herein, we report the study of the interaction of 3,4-dihydroxyhydrocinnamic acid (DHCA) functionalized IONPs that have desirable properties for T2 - weighted MRI, with bone marrow-derived primary human mesenchymal stem cells (hMSCs). Using the multiparametric high-content imaging method, we evaluate cell viability, formation of reactive oxygen species, mitochondrial health, as well as cell morphology and determine that the hMSCs are minimally affected after labelling with IONPs. Their cellular uptake is visualized by transmission electron microscopy (TEM) and Prussian Blue staining, and quantified using an iron specific colourimetric method. In vitro and in vivo studies demonstrate that these IONPs are biocompatible and can produce significant contrast enhancement in T2-weighted MRI. Iron oxide nanoparticles are detected in vivo as hypointense regions in the liver up to two weeks post injection using 9.4 T MRI. These DHCA functionalized IONPs are promising contrast agents for stem cell tracking by T2-weighted MRI as they are biocompatible and show no evidence of cytotoxic effects on hMSCs.